Precarious Professionals Gender, Identities and Social Change in Modern Britain - Egginton, Heidi; Thomas, Zoë (New Historical Perspectives, 2021)
Precarious Professionals uncovers the inequalities and insecurities which lay at the heart of professional life in nineteenth- and twentieth-century Britain. The book challenges conventional categories in the history of work, exploring instead the everyday labour of maintaining a professional identity on the margins of the traditional professions. Situating new historical perspectives on gender at the forefront of their research, the contributors explore how professional cultures could not only define themselves against, but often flourished outside of, the confines of patriarchal codes and structures. Putting the lives of precarious professionals in dialogue with master narratives in modern British history, the chapters in this volume re-evaluate the relationship between professional identity and social change. The collection offers twelve fascinating studies of women and men who held positions in art and science, high culture and popular journalism, private enterprise and public service between the 1840s and the 1960s. From pioneering women lawyers and scientists to ballet dancers, secretaries, historians, humanitarian relief workers, social researchers, and Cold War diplomats, the book reveals that precarity was a thread woven throughout the very fabric of modern professional life, with far-reaching implications for the study of power, privilege, and expertise. Together, these essays enrich our understanding of the histories and mysteries of professional identity and help us to reimagine the future of work in precarious times.